Stiff person syndrome and other immune-mediated movement disorders: new insights - Balint, Bettina (Current opinion in neurology, 2016)
Purpose of review This review highlights the recent developments in immune-mediated movement disorders and how they reflect on clinical practice and our understanding of the underlying pathophysiological mechanisms. Recent findings The antibody spectrum associated with stiff person syndrome and related disorders (SPSD) has broadened and, apart from the classic glutamic acid decarboxylase (GAD)- and amphiphysin-antibodies, includes now also antibodies against dipeptidyl-peptidase-like protein-6 (DPPX), gamma-aminobutyric acid type A receptor (GABAAR), glycine receptor (GlyR) and glycine transporter 2 (GlyT2). The field of movement disorders with neuronal antibodies keeps expanding with the discovery for example of antibodies against leucine rich glioma inactivated protein 1 (LGI1) and contactin associated protein 2 (Caspr2) in chorea, or antibodies targeting ARHGAP26- or Na+/K+ ATPase alpha 3 subunit (ATP1A3) in cerebellar ataxia. Moreover, neuronal antibodies may partly account for movement disorders attributed for example to Sydenham's chorea, coeliac disease, or steroid responsive encephalopathy with thyroid antibodies. Lastly, there is an interface of immunology, genetics and neurodegeneration, e.g. in Aicardi-Goutières syndrome or the tauopathy with IgLON5-antibodies. Summary Clinicians should be aware of new antibodies such as dipeptidyl-peptidase-like protein-6, gamma-aminobutyric acid type A receptor and glycine transporter 2 in stiff person syndrome and related disorders, as well as of the expanding spectrum of immune-mediated movement disorders.